Comparison of PSA to Moringa Oleifera Seed Protein as Sorbent in QuEChERS: A Response Surface Methodology Optimization for Extraction of Some Endocrine Disrupting Chemicals in Food. (13th September 2022) - Ramalepe, Thapelo; Richards, Heidi; Tutu, Hlanganani; Nuapia, Yannick; Chaúque, Eutilério; Nyambe, Imasiku; Chimuka, Luke
Abstract : This work aimed at optimizing the QuEChERS method with PSA and then comparing it with Moringa Oleifera seed protein as a clean-up sorbent for the extraction of endocrine-disrupting chemicals. The response surface methodology approach was used in the optimization. A design of experiment (DoE) was used to investigate the effect of the sample mass (0.5–3 g), centrifuge speed (3400–4000 rpm) and time (5–20 min), the mass of N a C l and MgSO 4 1 − 3 g, and solvent extraction volume (5–10 mL). The analysis was done using GC-ECD and GC × GC TOFMS. The PSA method which was later replaced with Moringa Oleifera seed protein presented optimal values of 3 g of sample, 150 mg PSA, 4000 rpm for 6 min centrifuge conditions, including 2 g NaCl and 2 g MgSO 4 extracted in 10 mL methanol, respectively. Moringa Oleifera seed protein gave better selectivity, and the detection limits ranged between 0.16 and 1.77 μ g kg − 1 with RSD values ≤ 13.32 %, respectively. Moreover, recoveries were between 76.2 ± 0.85% and 105.2 ± 2.24%. Application of the developed method in food samples detected some EDCs. This study has shown that Moringa Oleifera seed protein is a promising alternative to PSA in the clean-up of food-related samples using the QuEChERS approach.